A legal framework for the Jirga community mediation in Khyber Pakhtunkhwa - Ahmad, Muhamad Hassan; Khan, Ihtesham Ullah; Masum, Ahmad; Nafees, Seeni Mohamed (Faculty of Shariah & Law, International Islamic University, Islamabad, Pakistan, 2019)
Generally, in the Pushtoon community in Khyber Pakhtunkhwa (KP), neighbourhood disputes are resolved through the Jirga system which is the oldest and still one of the most typical dispute resolution mechanisms. Despite the importance of the Jirga system in ensuring the administration of justice and harmony in the Pushtoon community in various ways, it has also been subjected to several criticisms due to its informal structures which may sometimes lead to grave injustice to the parties or violate human rights. On the other hand, there is also no specific legal framework governing the community mediation. Authors are of the opinion that the government bodies should handle the administration of justice in accordance with the existing laws in KP rather than allowing some individuals with no proper knowledge on justice to settle the dispute by making use of the traditional Jirga system within their limited intellectual capacity which at times lead to grave human rights violations and injustices. Accordingly, this paper proposes a comprehensive legal framework which covers community mediation from all dimensions by giving importance to the traditional Jirga dispute resolution methods in place in KP and also learning experiences from other suitable jurisdictions.